ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA KECURANGAN PADA SEKTOR PEMERINTAHAN (STUDI PENELITIAN PADA KEMENTERIAN PERDAGANGAN) - Rio Prambudi; Bayu Dewangkoro; Susi Dwimulyani (Jurnal Magister Akuntansi Trisakti, 2017)
The purpose of this research is to probe the perception that employees on goverment institute on the influence of procedural equity, distribution equity, effectivenes of internal control, compensation match, organization culture, unetchical behaviour, and law enforcement towards frauds in the Ministry of Trade. The amount of samples in this reseach is 103 employees on Ministry of Trade office in Jakarta. The sampling technique used is convenience sampling. The data collected is from the questioner.The result of this result shows that there is negatif effect between procedural equity, distribution equity, effectiveness of internal control, compensation match, organization culture, law enforcement towards frauds in the government sector, positve effect from unetchical behaviour towards frauds in the government sector.